2010
DOI: 10.1128/jcm.01034-10
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Clarithromycin Resistance and cagA , vacA , iceA2 , and babA2 Genotypes of Helicobacter pylori in Brazilian Children

Abstract: We isolated 45 Helicobacter pylori strains from 217 child patients. Resistance to clarithromycin, metronidazole, amoxicillin, and tetracycline was detected in 27%, 13%, 4%, and 0% of strains, respectively. The A2143G mutation was the most prevalent (67%) among clarithromycin-resistant strains. In addition, strain genotyping revealed a significant association between gastritis severity and the simultaneous presence of cagA, vacA s1m1, iceA2, and babA2 genes.Helicobacter pylori infection is found worldwide and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
3
27
2
Order By: Relevance
“…The association of babA2 gene with different clinical outcomes has been shown in several studies. [13][14][15] Our findings are not in agreement with the study conducted by Arevalo-Galvis et al, who reported 57.0% of isolates were babA2 positive and more often found in patients with duodenal ulcer. Furthermore, other South American studies report that this gene frequency range from 46.0 to 82.3%.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…The association of babA2 gene with different clinical outcomes has been shown in several studies. [13][14][15] Our findings are not in agreement with the study conducted by Arevalo-Galvis et al, who reported 57.0% of isolates were babA2 positive and more often found in patients with duodenal ulcer. Furthermore, other South American studies report that this gene frequency range from 46.0 to 82.3%.…”
contrasting
confidence: 57%
“…14 Garcia et al, showed babA2 gene frequency in the Brazilian population is high, and is in association with various upper gastrointestinal diseases. 15 In Costa Rica, the prevalence of babA2 was 73.7%, which was higher than in Western studies (38.0-43.0%), but lower than that of Asian studies, also in Japanese patients (96.8%). 5 In Mexico, similar to our study, babA2 frequency is low (21.7%).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Similar percentages were found by studies conducted in Colombia and in Brazil. In the latter, only the iceA gene was discordant 38,39 . In patients with enanthematous gastritis, the combination of babA2/vacAs2m2/ iceA2 was detected in 22.6% (7/31).…”
Section: Discussionmentioning
confidence: 99%
“…The current data is consistent with the results reported in Poland (Maciorkowska et al, 2007) and Shanghai (Zhou et al, 2010) where the s1m2 was the most prevalent genotype. In contrast, other predominant vacA genotypes were reported in Brazil, Slovenia, the Mid-western United States (s1m1), and Spain (s2m2) (Podzorski et al, 2003;Homan et al, 2009;Agudo et al, 2010;Garcia et al, 2010).…”
Section: Discussionmentioning
confidence: 96%